Influence of sociocultural factors and acceptance of Creationism in the comprehension of evolutionary Biology in freshman brazilian students - Penteado, Pierre R.; Kavalco, Karine F.; Pazza, Rubens (Evolution: Education and Outreach, 2012)
The creationist movements in Brazil, although considered weak, are on the increase. The Brazilian legislation neither imposes any objection in teaching evolution nor obliges the teaching of creationism as an alternative to evolution in science classes. Furthermore, it allows the optional teaching of religion at schools. The aim of the present study was to evaluate the knowledge regarding biological evolution in freshman students from a Brazilian university. Such knowledge was related to sociocultural factors such as their parental education level, the type of high school the student graduated from (private or public school), their philosophical/religious position as well as the acceptance of creationism as an alternative to evolution. Among those factors, the latter two showed significant differences, in which the higher averages belonged both to the atheistic students and to those who do not accept creationism as an alternative to evolution.
Keywords: Science education; Teaching evolution; Intelligent Design; Religious position